2017
DOI: 10.1111/head.13037
|View full text |Cite
|
Sign up to set email alerts
|

Medication Overuse Headache: Pathophysiological Insights from Structural and Functional Brain MRI Research

Abstract: MOH is associated with atypical structure and function of brain regions responsible for pain processing as well as brain regions that are commonly implicated in addiction. Several studies have shown "normalization" of structure and function in pain processing regions following discontinuation of the overused medication and resolution of MOH. However, some of the abnormalities in regions also implicated in addiction tend to persist following discontinuation of the overused medication, suggesting that they are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 27 publications
3
36
0
3
Order By: Relevance
“…Of note, somatosensory cortex was also related to the total PCS score. Concerning FC, our findings highlight a distinct pattern of intra-cerebellar activation changes in association with regions, ACC, basal ganglia, somatosensory cortex (Fumal, Laureys et al 2006, Lakhan, Avramut et al 2013, Schwedt and Chong 2017, Messina, Rocca et al 2018. Considering that several MOH-related structural and/or functional abnormalities are reversible after withdrawal in contrast to orbitofrontal dysfunction (Fumal, Laureys et al 2006, Riederer, Gantenbein et al 2013, the influence of overused medication on the association between PC, GM density and functional connectivity is intriguing and needs clarification in future studies.…”
Section: Is the Whole Identical To Its Parts?mentioning
confidence: 51%
“…Of note, somatosensory cortex was also related to the total PCS score. Concerning FC, our findings highlight a distinct pattern of intra-cerebellar activation changes in association with regions, ACC, basal ganglia, somatosensory cortex (Fumal, Laureys et al 2006, Lakhan, Avramut et al 2013, Schwedt and Chong 2017, Messina, Rocca et al 2018. Considering that several MOH-related structural and/or functional abnormalities are reversible after withdrawal in contrast to orbitofrontal dysfunction (Fumal, Laureys et al 2006, Riederer, Gantenbein et al 2013, the influence of overused medication on the association between PC, GM density and functional connectivity is intriguing and needs clarification in future studies.…”
Section: Is the Whole Identical To Its Parts?mentioning
confidence: 51%
“…Physiological testing suggests that medication overuse produces facilitation of supraspinal nociceptive processing in the trigeminal and somatic sensory systems 31 . Imaging studies in MOH showed structural and functional brain changes within the pain processing networks and networks commonly linked to addiction, such as the mesocorticolimbic system 32‐34 . While reversal of some of these changes has been observed after withdrawal, others tend to persist and are interpreted as a predisposing brain trait 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Imaging studies in MOH showed structural and functional brain changes within the pain processing networks and networks commonly linked to addiction, such as the mesocorticolimbic system 32‐34 . While reversal of some of these changes has been observed after withdrawal, others tend to persist and are interpreted as a predisposing brain trait 34 . Experimental work showed that prolonged exposure to migraine treatments causes alterations in descending pain modulation, and on a cellular level changes in serotonergic transmission and receptor densities (eg, kappa opioid receptors) have been described 35‐37 …”
Section: Introductionmentioning
confidence: 99%
“…Eine Störung des endogenen Schmerzhemmsystems konnte bei chronischen Spannungskopfschmerzen (18), aber auch bei sekundären Formen wie dem Kopfschmerz bei Analgetikaübergebrauch (14) beschrieben werden. Studien zur funktionellen Bildgebung von Kopfschmerzen weisen bei idiopathischen (19)(20)(21) und symptomatischen Erkrankungen (22) auf Veränderungen in ähnlichen Hirnstrukturen bzw. -netzwerken hin.…”
Section: Wie Genau Kann Man Zwischen Idiopathischen Und Symptomatischunclassified